Reading psychoanalysis : Freud, Rank, Ferenczi, Groddeck - Rudnytsky, Peter L. (Cornell studies in the history of psychiatry., 2002)
In a stunning fusion of literary criticism and intellectual history, Peter L. Rudnytsky explores the dialectical interplay between literature and psychoanalysis by reading key psychoanalytic texts in a variety of genres. He maps the origins of the contemporary relational tradition in the lives and work of three of Freud's most brilliant and original disciples-Otto Rank, Sándor Ferenczi, and Georg Groddeck. Rudnytsky, a scholar with an unsurpassed knowledge of the world of clinical psychoanalysis, espouses the "relational turn" as an alternative to both ego psychology and postmodernism. Rudnytsky seeks to alter the received view of the psychoanalytic landscape, in which the towering figure of Freud has continued to obscure the achievements of his followers who individually resisted and collectively went beyond him. Reading Psychoanalysis offers the most detailed and comprehensive treatments available in English of such classic texts as Freud's case of Little Hans, Rank's The Incest Theme in Literature and Legend, and Groddeck's The Book of the It. Rudnytsky's argument for object relations theory concludes by boldly affirming the possibility of a "consilience" between scientific and hermeneutic modes of knowledge